Gender stereotypes and their correlates: the moderating role of voluntary sports club membership - Wicker, Pamela; Cunningham, George B. (Frontiers in Psychology, 2023)
This study examined the correlates of gender stereotypes and the moderating role of membership in a voluntary sports club. Drawing on the contact hypothesis, this study argues that gender stereotypes are lower when individuals regularly have the opportunity to meet and play sport with such people, for example in a voluntary sports club. Survey data from the European Values Study are used for the analysis (n=36,185; 30 countries). Gender stereotypes are measured with statements on gender role attributes. Regression results show that membership in a voluntary sports club, being a student, in-come, and living in a more gender equal country significantly reduce gender stereotypes. On the contrary, male gender, living in a partnership, having children, lower and medium education, part-time employment, self-employment, unemployment, being a home maker, and living in a small town are correlates of higher gender stereotypes. Interacting the latter correlates with sports club membership support its moderating effect in the sense that most correlates turn insignificant or have smaller coefficients. The only variables retaining their coefficient size are self-employment and living in a small town. The findings support the contact hypothesis and suggest that sports clubs are places that lessen gender stereotypes.